2018
DOI: 10.1111/1750-3841.14061
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid‐Based Oxygen Scavenger in Active Food Packaging System for Raw Meatloaf

Abstract: Oxygen-scavenging sachets containing iron powder have been generally used although those have several problems. Therefore, to solve them, an ascorbic acid-based oxygen scavenger composed of activated carbon and sodium l-ascorbate was newly developed. It did not only inhibit lipid oxidation but also reduce microbial growth in meatloaves. It could be used as a promising packaging material to protect meat products from lipid oxidation and microbial contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Vitamin C is more often used in active packages as an antioxidant agent [45,46]. Lee J-S. et al [46] have demonstrated higher oxygen scavenging properties of activated carbon-ascorbic acid active packaging than standard iron powder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin C is more often used in active packages as an antioxidant agent [45,46]. Lee J-S. et al [46] have demonstrated higher oxygen scavenging properties of activated carbon-ascorbic acid active packaging than standard iron powder.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C is more often used in active packages as an antioxidant agent [45,46]. Lee J-S. et al [46] have demonstrated higher oxygen scavenging properties of activated carbon-ascorbic acid active packaging than standard iron powder. In addition, they have shown that ascorbic acid active packaging significantly inhibited growth of aerobic bacteria, yeasts, and molds on meatloaves during 4 days of incubation at 4 • C [46].…”
Section: Discussionmentioning
confidence: 99%
“…For examples, Lee et al. () demonstrated that an oxygen scavenger retarded the lipid oxidation of raw meatloaf. Aday and Caner () showed that oxygen scavengers maintain the firmness of strawberries during storage.…”
Section: Introductionmentioning
confidence: 99%
“…It can be used to overcome the limitations of the metallic oxygen scavenger. However, the oxidation reaction of ascorbic acid is accompanied by production of CO 2 (Lee et al., ). Thus, the commercial metallic and nonmetallic oxygen scavengers are not appropriate for kimchi packaging.…”
Section: Introductionmentioning
confidence: 99%
“…16,18 One of the most common types of oxygen scavenger uses iron powder which reacts with oxygen to form iron oxide, allowing the reduction of residual oxygen in MAP packages from an initial value typically ranging from 0.3% to 3%, to below 0.01%. 16,17,19 Oxygen scavengers have been studied for storage of packaged fresh meats, [20][21][22][23] providing better colour, odour and lipid stability, and providing some inhibition to aerobic spoilage organisms. Grini et al 11 found superior colour stability during illuminated storage of sliced bologna sausage when oxygen scavengers were used.…”
mentioning
confidence: 99%